Reproducibility of Endometrial Volume by VOCAL in the Prediction of Success Rate of IVF/ICSI in Women with Unexplained Infertility - El-Shahawy Y (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2016)
Objective: To explore the role of estimating endometrial volume by Virtual Organ Computer-aided Analysis (VOCAL) and it's correlation with endometrial thickness, on the day of hCG, in prediction of IVF/ICSI success.  Patients and Methods: It was a prospective study that was carried out at Al-Amin Maternity Hospital, Saudi Arabia. Endometrial thickness and volume were measured in women undergoing an IVF/ICSI cycle, on the day of HCG, using the 3D trans vaginal ultrasound probe. Women were divided as regards to endometrial volume calculated into 3 subgroups; < 3 ml, 3-5 ml, and >5 ml, also according to endometrial thickness into 3 groups; <7 mm, 7-12 mm and >12 mm. Success rate of IVF/ICSI was compared between all groups.  Results: The current study included 150 consented women with no significant difference in clinicdemographic characteristics between all subgroups. The pregnancy rates between the three groups of endometrial volume; <3 ml, 3-5 ml, and >5 ml was; 28.6%, 29.9% and 25% respectively. Pregnancy rates between the three groups of endometrial thickness was 18.2%, 25.5% and 43.3% for <7 mm, 7-12 and >12 mm respectively. There was no significant difference in pregnancy rates between all groups in relation to both endometrial volume and endometrial thickness.  Conclusions: Endometrial thickeness on day of hCG is a better predictor of success rate of IVF/ ICSI cycles than endometrial volume.